Modern fairies, dwarves, goblins, and other nasties : a practical guide - Blume, Lesley M. M. (Alfred A. Knopf, 2010)
A compendium of practical information and cautionary tales about fairies and other similar magical creatures that might be encountered in modern cities like New York, intended to help the child who may come into contact with them.